Macrophages in periapical lesions: Potential roles and future directions - Song, Yao; Li, Xinying; Huang, Dingming; Song, Hongjie (Frontiers in Immunology, 2022)
Periapical lesions are infectious diseases that occur in the apical region of teeth. They result in the destruction of alveolar bone and are usually accompanied by swelling, pain, and possible systemic impacts. A complex interaction between pathogens and the host immune system determines the development, progression, and outcome of periapical lesions. The lesions, if not treated promptly, may cause resorption of bone tissue, destruction of the periodontal ligament, and loss of the affected teeth, all of which can severely worsen the quality of life of patients, often at considerable economic cost to both patients and medical organizations. Macrophages are a group of heterogeneous cells that have many roles in the development of infections, destruction and reconstruction of bone tissues, and microbe–host interactions. However, the differential and comprehensive polarization of macrophages complicates the understanding of the regulatory mechanism of periapical lesion progression. This report provides a comprehensive review of recent advances in our knowledge of the potential role of macrophages in determining the turnover of human periapical lesions. For example, macrophage differentiation might indicate whether the lesions are stable or progressing while the extent of bacteria invasion could regulate the differentiation and function of macrophages involved in the periapical lesion. In addition, alternative strategies for the treatment of apical periodontitis are discussed.